ASAS/EULAR recommendations for the management of ankylosing spondylitis. Issue 4 (26th August 2005) - Zochling, J; van der Heijde, D; Burgos-Vargas, R; Collantes, E; Davis, J C; Dijkmans, B; Dougados, M; Géher, P; Inman, R D; Khan, M A; Kvien, T K; Leirisalo-Repo, M; et al.
Abstract : Objective: To develop evidence based recommendations for the management of ankylosing spondylitis (AS) as a combined effort of the 'ASsessment in AS' international working group and the European League Against Rheumatism. Methods: Each of the 22 participants was asked to contribute up to 15 propositions describing key clinical aspects of AS management. A Delphi process was used to select 10 final propositions. A systematic literature search was then performed to obtain scientific evidence for each proposition. Outcome data for efficacy, adverse effects, and cost effectiveness were abstracted. The effect size, relative risk, number needed to treat, and incremental cost effectiveness ratio were calculated. On the basis of the search results, 10 major recommendations for the management of AS were constructed. The strength of recommendation was assessed based on the strength of the literature evidence, risk-benefit trade-off, and clinical expertise. Results: The final recommendations considered the use of non-steroidal anti-inflammatory drugs (NSAIDs) (conventional NSAIDs, coxibs, and co-prescription of gastroprotective agents), disease modifying antirheumatic drugs, treatments with biological agents, simple analgesics, local and systemic steroids, non-pharmacological treatment (including education, exercise, and physiotherapy), and surgical interventions. Three general recommendations were also included. Research evidence (categories I–IV) supported 11 interventions in the treatment of AS. Strength of recommendation varied, depending on the category of evidence and expert opinion. Conclusion: Ten key recommendations for the treatment of AS were developed and assessed using a combination of research based evidence and expert consensus. Regular updating will be carried out to keep abreast of new developments in the management of AS.